Comparison of pain perception, anxiety, and impacts on oral health-related quality of life between patients receiving clear aligners and fixed appliances during the initial stage of orthodontic treatment. (2nd July 2020) - Gao, Meiya; Yan, Xinyu; Zhao, Rui; Shan, Yue; Chen, Yiyin; Jian, Fan; Long, Hu; Lai, Wenli
Abstract: Background and Objectives: Clear aligner is an advanced orthodontic method with benefits of comfort, aesthetics, and convenience. This study aimed to compare pain perception, anxiety, and impacts on oral health-related quality of life (OHRQoL) between adult patients receiving clear aligners and fixed appliances during the initial stage of orthodontic treatments. Material and Methods: The two groups were well matched by ages, gender, and levels of malocclusion severity. Pain perception, anxiety, and OHRQoL were assessed through visual analogue scale, state-trait anxiety inventory, and oral health impact profile-14 (OHIP-14), respectively. And the comparison of above scores was performed by two-way analysis of variance. Results: A total of 110 patients (55 pairs) were enrolled in this study. Orthodontic pain levels peaked on the first day and decreased gradually afterwards in both groups, which were significantly higher in the fixed group on the first, second, fourth, and fifth days. Likewise, anxiety levels peaked on the first day and decreased thereafter, with significant difference on the 1st, 3d, 5th, 7th, and 14th days. Moreover, the OHIP-14 scores increased and peaked on the first day and then gradually decreased for both groups, which were also significantly higher in the fixed group on the 1st, 7th, and 14th days. Limitations: More malocclusion types should be used for group matching. The effect of exclusion of small groups should be taken into consideration in sample size calculation. Income was significantly unbalanced between two groups due to higher cost of clear aligners, and random assignment of treatment modalities was unfeasible. Conclusions: Patients treated with clear aligners experienced lower pain levels, less anxiety, and higher OHRQoL as compared to those receiving fixed appliances.